THE LINEAR SPEED OF THE WORKPIECE MOVEMENT MEASURING METHOD THAT AN INDUCTOSYN-TYPE MEASURING TRANSDUCER USING - KHRULOV, MYKOLA; KRYVOUS, HENNADII (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article considers a method for measuring the linear speed of movement of the workpiece using an inductosyn-type measuring transducer. To ensure the implementation of technological processes, it is required to maintain the values of technological parameters within the specified limits. One of the important parameters of many technological processes is the speed of movement of the working body relative to the workpiece. One of the areas of application of speed sensors are numerical control systems, in which speed sensors are used to control the electric drive. Currently, a significant amount of CNC equipment is in operation, in which movement meters that use the transformation of angular displacement into phase and are made on the basis of primary transducers such as inductosyn, resolver, rotating transformer or selsyn are used.It is proposed to measure the linear speed of the workpiece movement using an inductosyn type measuring transducer by measuring the angular velocity of the inductosyn rotor, which is defined as the difference of the angular velocity of the rotating magnetic field created by the stator windings and the angular velocity of the rotor, relative to the rotating magnetic field of the stator. It is noted that if the direction of rotation of the magnetic field and the direction of rotation of the rotor is matching, and if the angular velocities of rotation of the magnetic field and the rotor are equal, the proposed method for measuring the linear velocity of the workpiece cannot be used. The application of the proposed method will allow to eliminate additional devices, that is necessary to determine the speed of movement of the workpiece, for example, tachometers, which will significantly reduce the cost of movement speed meters based on inductosyn.
Keywords: measurement method; movement speed measurement; transducer; inductosyn